PENGARUH FASILITAS KANTOR DAN DISIPLIN KERJA TERHADAP KINERJA PEGAWAI DESA SUKAMAJU KECAMATAN JONGGOL - Sindy Putri Winardi; Rini Wijayanti (Jurnal Ilmiah Global Education, 2023)
This study aims to determine the effect of office facilities and work discipline on the performance of employees of Sukamaju Village, Jonggol District. This study used descriptive qualitative method. The techniques used in collecting data in this study included observation, interviews and documentation directly to respondents at the Sukamaju Village office. The results showed that the office facilities and discipline in this study had a significant impact on employee performance. Based on the results of observiews with informants, office facilities and discipline are only quite good, but employee performance is still very low, in terms of the level of effectiveness of employee performance, which averages only 59%.